2019
DOI: 10.1002/ajpa.23829
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of sexual dimorphism in ribcage kinematics of modern humans

Abstract: Objectives: Sexual dimorphism is an important biological factor underlying morphological variation in the human skeleton. Previous research found sex-related differences in the static ribcage, with males having more horizontally oriented ribs and a wider lower ribcage than females. Furthermore, a recent study found sex-related differences in the kinematics of the human lungs, with cranio-caudal movements of the caudal part of the lungs accounting for most of the differences between sexes. However, these moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 73 publications
(130 reference statements)
2
23
0
Order By: Relevance
“…Our results show that torso morphology and thoraco‐pelvic covariation in adult H. sapiens individuals are mainly driven by sexual dimorphism, with relatively wider (lower) thoraces than (upper) pelves in males and the opposite trend in females (Figures 2, 3a and 6a, Table 3). These results replicate the findings of Torres‐Tamayo et al (2018) and are consistent with previous works showing that sexual dimorphism plays an important role in the thorax and pelvis shape variation in H. sapiens (Bellemare et al, 2003; Fischer & Mitteroecker, 2017; García‐Martínez et al, 2016, 2019; Gruss & Schmitt, 2015; K. Rosenberg & Trevathan, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results show that torso morphology and thoraco‐pelvic covariation in adult H. sapiens individuals are mainly driven by sexual dimorphism, with relatively wider (lower) thoraces than (upper) pelves in males and the opposite trend in females (Figures 2, 3a and 6a, Table 3). These results replicate the findings of Torres‐Tamayo et al (2018) and are consistent with previous works showing that sexual dimorphism plays an important role in the thorax and pelvis shape variation in H. sapiens (Bellemare et al, 2003; Fischer & Mitteroecker, 2017; García‐Martínez et al, 2016, 2019; Gruss & Schmitt, 2015; K. Rosenberg & Trevathan, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…They used 3D geometric morphometrics (GMM) of sliding semilandmarks for analyzing 50 torso 3D models segmented from thoraco‐abdominopelvic computed tomography (CT) scans of two different adult populations, and found that modern human females showed mediolaterally narrower (lower) thoraces than their wide (upper) pelves and modern human males showed the opposite trend in both populations. These authors reported that sexual dimorphism would be the main factor driving thoraco‐pelvic covariation in adult H. sapiens , and their results are consistent with those of previous studies analyzing sex‐related variation in the thorax and pelvis separately (Bellemare et al, 2003; Fischer & Mitteroecker, 2015, 2017; García‐Martínez et al, 2016, 2019; LoMauro & Aliverti, 2018; Molgat‐Seon, Peters, & Sheel, 2018). Thus, Torres‐Tamayo et al (2018) proposed a new and more complex torso integration model in H. sapiens (torso integration hypothesis) that called into question the correspondence between a narrow thorax and a narrow pelvis classically reported for this species (Lovejoy, 2005; Middleton, 2013, 2015, 2017; Schultz, 1950, 1961; C. V. Ward, 1993).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Ribcages were segmented through a semi-automatic protocol for Digital Imaging and Communication On Medicine (DICOM) images using the 3D Slicer software (www.slicer.org/) and subsequently reconstructed as 3D models. These 3D models were imported into Viewbox4 software (www.dhal.com) for (semi-) landmarking using existing protocols (60). Thoracic morphology was quantified through 20 homologous 3D landmarks and semilandmarks on ribs 1 to 10 and 19 3D landmarks and semilandmarks on ribs 11 and 12.…”
Section: Methodsmentioning
confidence: 99%